KETERSEDIAAN LOGISTIK KESEHATAN DALAM KESIAPSIAGAAN MENGHADAPI BENCANA (STUDI KASUS DI DINAS KESEHATAN KABUPATEN NAGAN RAYA) - Joharuddin, Joharuddin; Ketaren, Otniel; Hutajulu, Johansen; Nababan, Donal; Ester J. Sitorus, Mido (Universitas Pahlawan, 2023)
Disaster events can cause health crises, such as deaths, injuries, illnesses, refugees, paralysis of health services, infectious diseases, environmental sanitation, mental disorders and other health problems. Meanwhile, the provision of health services during disasters often faces obstacles due to inadequate numbers and types of medicines and medical equipment, limited human resources and health clusters, as well as operational funds so that health logistics are needed. This type of research is qualitative research with a phenomenological approach. The research was carried out at the Nagan Raya District Health Service from March to August 2023. There were 5 informants in this study, namely the head of the health service, the secretariat, the human resources sector, the head of the pharmaceutical installation, and the administration of the pharmaceutical installation sub-section. Data collection techniques were carried out through in-depth interviews and observation. The results of the research show that planning at the Nagan Raya District Health Service has carried out good planning, seen from the work program, and evaluation of activities as well as the establishment of coordination between the Health Service and the community health centers. The procurement of health logistics is good and comes from the Regency ABPD which has been evaluated by the DPRD. Warehousing or health logistics storage already exists, but warehousing is inadequate and still needs improvement. Distribution is good, and there is cross-sector collaboration, distribution by the TNI/POLRI is very dominant.